Value streams in microgrids: A literature review. (15th January 2016) - Stadler, Michael; Cardoso, Gonçalo; Mashayekh, Salman; Forget, Thibault; DeForest, Nicholas; Agarwal, Ankit; Schönbein, Anna
Highlights: This paper presents a review on current literature relevant to microgrid revenue streams. A microgrid definition is presented along with requirements that increase deployment costs. Both direct and indirect revenue streams are discussed. Demand response, net metering and power exports, and value of increased resiliency are discussed. Potential local energy markets are also addressed. Abstract: Microgrids are an increasingly common component of the evolving electricity grids with the potential to improve local reliability, reduce costs, and increase penetration rates for distributed renewable generation. The additional complexity of microgrids often leads to increased investment costs, creating a barrier for widespread adoption. These costs may result directly from specific needs for islanding detection, protection systems and power quality assurance that would otherwise be avoided in simpler system configurations. However, microgrids also facilitate additional value streams that may make up for their increased costs and improve the economic viability of microgrid deployment. This paper analyses the literature currently available on research relevant to value streams occurring in microgrids that may contribute to offset the increased investment costs. A review on research related to specific microgrid requirements is also presented.